Infrastructure and Economic Growth in Asia - Cockburn, John; Dissou, Yazid; Duclos, Jean-Yves; Tiberti, Luca (Economic Studies in Inequality, Social Exclusion and Well-Being, 2013)
Development Economics; Economic Growth; Public Economics